Studies used TAM Framework as a guideline for the research: Literature Review - Alharbi, Omran; Alsheehri, Nada (Advances in Social Sciences Research Journal, 2021)
Several researchers have adopted theoretical framework such as Technology Acceptance Model (TAM) in order to gent in depth information about the phenomenon that under investigation. This literature review will focus on the papers that adopted TAM framework in their studies in order to understanding which are the most factors that affected behavioral intention to use technology by users. The results of this literature review find out that Perceived Eas of Use and Perceived Usefulness are the most elements that influenced the behavioral intention to use technology.